Mental health of the elderly: perceptions related to aging - Lais Soares Vello; Maria Alice Ornellas Pereira; Regina Célia Popim (Universidad de Antioquia, 2014)
Objective. To understand the elderly's perception of their current condition. Methodology. Study undertaken in 2012 using the qualitative method of Minayo and the thematic analysis according to Bardin's suggestions. Data were collected through semi-structured interviews that took place in the homes of the elderly people. The guiding question was: At this point in your life, how do you feel? Tell me. Results. The elderly who were satisfied stated that this was due to the good relationship with their family, spouse, to the fact of having autonomy and respect from the society. Those who were shown to be dissatisfied reported lack of family support, physical limitations imposed by age and the presence of illnesses as the main causes. Conclusion. The adult population requires the use of care technologies that cover all the stages of life, including old age. Nursing professionals should be prepared for the increasing care demand of these people.